Structure and Properties of Ti-Al Intermetallic Coatings Reinforced with an Aluminum Oxide Filler - Artem Igorevich Bogdanov; Vitaliy Pavlovich Kulevich; Victor Georgievich Shmorgun; Leonid Moiseevich Gurevich (Metals)
In this paper, the results of a study of the structure and phase composition of the hot-dip aluminizing coatings formed on the commercially pure titanium surface in AW-6063 aluminum alloy melt after heat treatment at 700 and 850 °C are presented. It is shown that as a result of aluminizing on the titanium surface, a homogeneous coating 30–40 µm thick without defects is formed. The hot-dip aluminizing coating consists of aluminum and the intermetallic compound TiAl3, located at the boundary with the substrate. Heat treatment results in the formation of a heterogeneous coating structure: its outer layer has a frame-type structure consisting of TiAl3 particles surrounded by an Al2O3 + TiO2 grid, and the inner continuous layer adjacent to the titanium consists of TiAl2, TiAl, and Ti3Al intermetallic layers. Increasing in the heat treatment temperature and/or holding time results in an increase in the thickness of both the outer and boundary layers of the coating. A mechanism for the formation of the coating structure via heat treatment is proposed. The scratch test method was used to evaluate the cohesive and adhesive strength of the coatings, and their scratch hardness was determined, which averaged 200 MPa. It was shown that the coating structure formed during heat treatment at 850 °C ensures higher resistance to cohesive failure.